2019
DOI: 10.22219/jpbi.v5i1.7626
|View full text |Cite
|
Sign up to set email alerts
|

Critical thinking skills: The academic ability, mastering concepts, and analytical skill of undergraduate students

Abstract: Science and technology development in the 21 st -Century has been demanding educators to provide learning activities which stimulate students' critical thinking skills. This study aimed to find out the correlated factors of the students' critical thinking skills as well as of which was the strongest determinant in leveling the skills. The subject of this correlational research was 112 undergraduate students in the Department of Biology Education, Universitas Muhammadiyah Malang who took Botany course. There we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
30
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(44 citation statements)
references
References 25 publications
2
30
0
5
Order By: Relevance
“…The results of ANCOVA analysis also found that there was a significant difference in critical thinking skills among the upper, middle and lower academic ability pre-service teachers. This finding supports the results of previous research reporting that differences in academic ability can affect the pre-service teachers' ability at criticizing information (D'Alessio et al, 2019;Mahanal et al, 2019;Permana et al, 2019;Zubaidah et al, 2018).…”
Section: The Effect Of Academic Ability and Critical Thinking Skillssupporting
confidence: 91%
See 3 more Smart Citations
“…The results of ANCOVA analysis also found that there was a significant difference in critical thinking skills among the upper, middle and lower academic ability pre-service teachers. This finding supports the results of previous research reporting that differences in academic ability can affect the pre-service teachers' ability at criticizing information (D'Alessio et al, 2019;Mahanal et al, 2019;Permana et al, 2019;Zubaidah et al, 2018).…”
Section: The Effect Of Academic Ability and Critical Thinking Skillssupporting
confidence: 91%
“…The academic ability itself is illustrated with academic performance (D'Alessio et al, 2019) and learning achievement (Fong et al, 2017). Academic ability is believed to be associated with critical thinking skills (Alkharusi, 2019;Permana et al, 2019;Tanujaya et al, 2017). Upper academic ability pre-service teachers generally have sufficient prior knowledge, so that they tend to have better critical thinking skills than the lower academic ability (Mahanal et al, 2019;Zubaidah et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Pembelajaran biologi tidak boleh hanya sekedar mengingat dan memahami karena pembelajaran yang seperti ini akan mengarah pada kemampuan menghafal materi (Septy et al, 2015). Keterampilan berpikir kritis merupakan salah satu keterampilan berpikir tingkat tinggi yang menuntut mahasiswa untuk mengunakan level kognitif tingkat analisis, evaluasi, dan mencipta (Permana et al, 2019). Pratama et al (2017); Zulfaneti et al (2018) dan Bustami et al (2019) menjelaskan bahwa keterampilan berpikir kritis berkaitan dengan pengambilan keputusan, perencanaan strategis, proses ilmiah, dan penyelesaian masalah untuk menemukan solusi.…”
unclassified